Spatio-temporal movement of water and nitrate under different dripper discharges in drip fertigation - KUMAR, MUKESH; RAJPUT, T B S; PATEL, NEELAM (The Indian Journal of Agricultural Sciences, 2016)
Fertigation is an advanced and efficient method of application of nutrients with irrigation water to the crop. Water and nutrient distribution in soil is one of the most important parameters to design efficient fertigation system. A field research was conducted to investigate the effect of dripper discharge at different system operating pressures on spatio-temporal soil moisture movement. The value of moisture contents varied significantly (P